Primary tuberculous osteomyelitis of the mandible mimicking odontogenic infection: A case report - Yogesh Kini; Gaurav Tomar; Aastha Maini; V. Bhagyasree; Hardik Mehta (Elsevier, 2021)
Tuberculosis (TB) although a rare disease in the developed countries, is still a serious problem in developing countries. Incidence of tuberculous osteomyelitis of the jaw bones is very low. The rare incidence and its clinical presentation frequently leads to misdiagnosis during initially management.We report a case of a 36-year-old male who presented with a draining sinus over the right side mandible since 3 months which later proved to be tuberculous osteomyelitis in absence of a primary focus and which responded well to anti-tubercular treatment (ATT).